2017
DOI: 10.1210/jc.2016-3437
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Transforming Growth Factor-β Activity in the Endometrium of Women With Heavy Menstrual Bleeding

Abstract: Context:Heavy menstrual bleeding (HMB) is common and incapacitating. Aberrant menstrual endometrial repair may result in HMB. The transforming growth factor (TGF)-β superfamily contributes to tissue repair, but its role in HMB is unknown.Objective:We hypothesized that TGF-β1 is important for endometrial repair, and women with HMB have aberrant TGF-β1 activity at menses.Participants/Setting:Endometrial biopsies were collected from women, and menstrual blood loss objectively measured [HMB >80 mL/cycle; normal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…In addition, they also demonstrated a decrease in Smad2 and Smad3 mRNA and levels of their corresponding phosphoproteins in women with HMB. The findings of the current study are more consistent with those of Maybin et al (2017), and any differences may be due to differences in methodology, menstrual cycle groupings, and classification of HMB. Maybin et al (2017) used an empirical definition of HMB with 80 mL menstrual blood loss as the cut off, whereas blood loss was not objectively measured in our study, and we used the current clinical assessment of patient declared HMB; thus, the classification used in the current study was more subjective.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, they also demonstrated a decrease in Smad2 and Smad3 mRNA and levels of their corresponding phosphoproteins in women with HMB. The findings of the current study are more consistent with those of Maybin et al (2017), and any differences may be due to differences in methodology, menstrual cycle groupings, and classification of HMB. Maybin et al (2017) used an empirical definition of HMB with 80 mL menstrual blood loss as the cut off, whereas blood loss was not objectively measured in our study, and we used the current clinical assessment of patient declared HMB; thus, the classification used in the current study was more subjective.…”
Section: Discussionsupporting
confidence: 79%
“…Abberton et al (1999b) demonstrated no difference in TGFβ1 immunoreactivity in an immunohistochemical study of endometrium from control women and those with HMB. More recently, Maybin et al (2017) reported no difference in mRNA levels for TGFβ1, TGFβRI, or TGFβRII in endometrium of women with HMB compared with controls. However, they did demonstrate a decrease in immunoreactivity for TGFβ1 in the stromal cells of women with HMB compared with controls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Menstrual blood loss (MBL) was objectively measured in the women providing endometrial tissue using a modified alkaline haematin method ( Hallberg & Nilsson 1964 , Maybin et al 2017 ) and heavy menstrual bleeding (HMB) defined as a blood loss of >80 mL per cycle. Women were given the same brand of menstrual products (Tampax® tampons/Always® towels, Proctor & Gamble, UK) with verbal and written instruction on collection.…”
Section: Methodsmentioning
confidence: 99%
“…TGFβ1 is involved with phenotype switching of VSM cells to a contractile phenotype and is also required for repair of the denuded menstrual endometrium 101 . There is evidence of decreased TGFβ1 bioavailability and signalling in the endometrium of women with HMB 101,102 , suggesting that TGFβ1 signalling and bioavailability could be potential therapeutic targets for the treatment of HMB in the future.…”
Section: Control Of Endometrial Bleedingmentioning
confidence: 99%